Survey the Crystal Type and Physiochemical properties of Isolated Starch Form Some Iraqi and Imported Genotypes of Corn (Zea Mays) Cultivated in Sulaimani-Iraq - Tarkhani, Maki Mohammed Ahmad; Zainulabidden, Muhammad Wajeeh M. Saeed (Journal of Kerbala for Agricultural Sciences, 2023)
The objective of this study is to conduct a survey comparing ten different genotypes of corn. (zea mays L.) cultivated in Qlyassan research station of College of Agricultural Engineering Science, were to find out the type of crystalline form of starch extracted from studied corn genotypes. There were significant differences between the studied corn genotypes in the chemical composition, especially amylose and amylopectin, in which the amylose range was between 19.935 and 31.095 there were also differences in the mean sizes of the starch granules which was 12.795 to 15.915 m, as well as for Gel consistency, despite of significant differences between corn genotypes starch, all genotypes undergo to soft gel consistency, but all of these were not have affects the type of amyloid crystal, which was type A.